Medical care for children in educational institutions: state, problems and prospects of development - T.V. Peresypkina; T.P. Sidorenko; A.M. Peresypkina; M.O. Kindruk (Zaslavsky O.Yu., 2018)
The article analyzes the systems of medical support for school-age children, features of organization. International experience shows that there are different models of medical care for children in educational institutions. The main differences relate to the subordination of the school service (health or education structures), funding, training and the greatest differences - in terms of preventive care: the volume and timing of preventive medical examinations. World Health Organization notes that now the optimal model of school health care in the world is not defined. The general problems of school health are the lack of funding, uneven access of children to medical services. The state of medical provision of schoolchildren in the post-Soviet countries is considered, as well as the results of the restructuring in the field of children health care related to the reform of the sanitary and epidemiological institutions system, the modernization of their functions, the creation of new vertical structures, the functions of which is the development of national and regional programs for promoting healthy lifestyle, medical education and communication activities. The development of the system of school medicine in Ukraine was analysed from the point of view of the "Concept of quality standards of school health services and competences" of the European Union for School and University Health and Medicine. The prospects of school medicine in Ukraine are outlined. Namely, the need to develop and implement a new Ukrainian model of school medicine adapted to European standards and integrate it into the public health system, which is approved in Ukraine; updating the regulatory framework; development of personnel potential; formation of new professional competencies of healthcare workers in school medicine in Ukraine; strengthening the interagency cooperation in helping children and adolescents maintain their health.